What can be expected from Social Theory in the Era of Post-metaphysics? - Murphy, John W. W. (Sociologija. Mintis ir veiksmas, 2013)
There are many complaints nowadays about social theory. On the one hand, theory is considered to be too abstract. The thrust of this approach, accordingly, is to develop a grand scheme that details how society or some component operates. Others argue, on the other hand, that theory is not abstract enough. These critics contend that theory is too particularistic and deals with simply how persons respond to themselves and others. Hence the focus is on interaction within very restricted confines. Each viewpoint merely begins from a different source. By invoking an actual debate that occurred in sociology, the thrust of this paper is to illustrate why the question of abstraction haunts theory. Additionally, an important issue that must be clarified is whether theory has any role without the ability to make generalized or increasingly abstract claims about social life. Keywords: social theory, the question of abstraction, Post-metaphysical Era.